Vagal regulation and internalizing psychopathology among adolescents exposed to childhood adversity. Issue 5 (11th December 2013) - McLaughlin, Katie A.; Alves, Sonia; Sheridan, Margaret A.
ABSTRACT Childhood adversity (CA) is strongly associated with youth psychopathology. Identifying factors that reduce vulnerability following CA is critical for developing preventive interventions. Vagal tone and vagal reactivity following psychosocial stressors might influence psychopathology among youths exposed to CA. We acquired heart period and impedance cardiography data to calculate respiratory sinus arrhythmia (RSA) and preejection period (PEP) from 157 adolescents aged 13–17 years at rest and during the Trier Social Stress Test (TSST). Internalizing and externalizing symptoms and multiple forms of CA were assessed. Resting RSA and RSA reactivity interacted with CA in predicting internalizing but not externalizing psychopathology; CA was unassociated with internalizing problems in adolescents with high resting RSA and RSA reactivity. No interactions were observed with PEP. High resting RSA predicted greater vagal rebound and accelerated heart rate recovery following the TSST, highlighting one potential mechanism underlying low internalizing symptoms following CA among youths with high vagal tone. © 2013 Wiley Periodicals, Inc. Dev Psychobiol 56: 1036–1051, 2014.